An Evaluation of the use of ADR in the Nigerian Public Construction Project Disputes - Idowu, Falilat Olubunmi; Ogunbiyi, Oyedolapo; Hungbo, Anthony Akinola (International Journal of Sustainable Construction Engineering and Technology, 2015)
Today’s construction projects are becoming more complex and more capital intensive. Governments of developing countries of the world are responsible for the provision of infrastructural facilities to its citizenry. Many researchers have however found that these projects are delivered late by contractors and disputes have been found as a major cause of such late deliveries. Disputes have also been found as a cause of cost overruns on construction projects. Therefore the use of ADR (Alternative Dispute Resolution) in resolving construction disputes cannot be over emphasized. This study examines the issues which militate against the use of ADR as well as the ADR techniques which give satisfaction to disputants in terms of cost, time and maintenance and sustainability of relationship. The study gathered information from both primary and secondary sources. Data from primary sources were collected from fifty seven construction and legal practitioners in the public and contracting organisations with the use of questionnaires. The sampling technique that was employed was stratified simple random sampling and data was analysed with the use of SPSS. The study found Lack of awareness of ADR as one of the factors that militate against the use of ADR. The ADR techniques which give satisfaction to disputants in terms of cost, time and maintenance and sustainability of relationship are adjudication and negotiation respectively. The study recommends that awareness of ADR techniques in resolving construction dispute should be increased in order to maximize the full benefit of the use of ADR in construction projects.